2018
DOI: 10.1111/teth.12456
|View full text |Cite
|
Sign up to set email alerts
|

Tabletop games and 21st century skill practice in the undergraduate classroom

Abstract: In the undergraduate classroom, tabletop games can aid both teaching and learningespecially when accompanied by debriefing exercises following gameplay. In particular, tabletop games enable undergraduate learners to practice the 21st century skills of collaboration, communication, and critical thinking. This qualitative study examines three cases from the disciplines of practical theology, systematic theology, and history, utilizing the methods of classroom video recordings, written assessments from students a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The fact that it is a research subject, especially with its 21st-century skills, can be interpreted as its density and decrease recently, and its popularity has decreased with long research. However, due to being an important variable (Hayse, 2018;Voogt et al, 2018), although the rate of increase has decreased, it has still been the subject of much research and can be interpreted as it will continue to be examined in research because it is an important skill.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that it is a research subject, especially with its 21st-century skills, can be interpreted as its density and decrease recently, and its popularity has decreased with long research. However, due to being an important variable (Hayse, 2018;Voogt et al, 2018), although the rate of increase has decreased, it has still been the subject of much research and can be interpreted as it will continue to be examined in research because it is an important skill.…”
Section: Discussionmentioning
confidence: 99%
“…Tabletop games of all sorts have been used to practise skills in classroom and generalized instructional situations. Skills including critical thinking abilities, communication, and collaboration have been practised in classroom situations, such as those described by Hayse (2018), and in library training, such as in Giles et al (2019). Students in Hayse's research reported generally feeling that the game-based activities increased engagement and specific skills.…”
Section: The State Of Educational Playmentioning
confidence: 99%
“…Given such rapid changes in technology, ideas, and concepts, we should aim to attract children's minds by designing curriculum and content that maintains their attention. Teachers must apply flexible and systematic thinking in line with the current situation and take students as a center that needs to be motivated to promote their long-term memory and computational thinking [2,3]. However, teachers are required to prepare for lessons beforehand, and, therefore, use their wisdom to flexibly grasp of students' attention and integrate suitable tabletop games into the curriculum before teaching to enhance students' learning motivations and effectiveness.…”
Section: Introductionmentioning
confidence: 99%